Micawber Capital : for mission or profit? - Austen-Smith, David, (SAGE knowledge. Cases., 2016)
In July 2010 Robert Drake, senior director at Micawber Capital, one of India's largest microfinance organizations, needed to recommend a corporate structure and organization for Micawber after its scheduled IPO in August 2010. The IPO would bring to Micawber new stakeholders, primarily financial institutions. Drake was skeptical that the new investors shared Micawber's commitment to help alleviate poverty in rural India through microcredit loans; he assumed their primary interest was a good return on their investments. This case outlines how Micawber set about resolving these two contradictory objectives.